2015
DOI: 10.1021/acs.jpcb.5b04164
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Infrared Spectroscopic Studies Provide Insight into Reactions of the NiFe Regulatory Hydrogenase from Ralstonia eutropha with O2 and CO

Abstract: The regulatory hydrogenase (RH) from Ralstonia eutropha acts as the H2-sensing unit of a two-component system that regulates biosynthesis of the energy conserving hydrogenases of the organism according to the availability of H2. The H2 oxidation activity, which was so far determined in vitro with artificial electron acceptors, has been considered to be insensitive to O2 and CO. It is assumed that bulky isoleucine and phenylalanine amino acid residues close to the NiFe active site "gate" gas access, preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…41,42 Observation of a stable Ni a -L state under “physiologically relevant” conditions is therefore not a prerequisite for involvement of Ni a -L in the catalytic cycle. This could have implications for the catalytic relevance of Ni a -L in O 2 -sensitive Group 1 hydrogenases, and the Group 2 RH from R. eutropha , where Ni a -L species have so far only been observed following photolysis of Ni a -C. 1,40,82 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 Observation of a stable Ni a -L state under “physiologically relevant” conditions is therefore not a prerequisite for involvement of Ni a -L in the catalytic cycle. This could have implications for the catalytic relevance of Ni a -L in O 2 -sensitive Group 1 hydrogenases, and the Group 2 RH from R. eutropha , where Ni a -L species have so far only been observed following photolysis of Ni a -C. 1,40,82 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that solution assays on this enzyme demonstrated catalytic H 2 oxidation (albeit with a very low turnover frequency), the Ni a -R state(s) were not observed upon treatment with H 2 , 82,83,87 or electrochemical reduction in solution. 86 This lead to suggestion of a distinct two-state catalytic cycle for this enzyme involving only Ni a -SI and Ni a -C. 1,3 Recently, however, PFIRE spectra have revealed the presence of at least one Ni a -R state during catalytic H 2 oxidation, 40 suggesting that a common set of redox levels is conserved across the [NiFe] hydrogenases from quite different Groups.…”
Section: Experimental Evidence For States Involved In the [Nife] Hydrmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, homogeneous distribution and orientation of enzymes in the 3D network is rarely achieved. Nonetheless, it is worth mentioning the original work of Vincent's group, who set up a Protein Film Infrared Electrochemistry (PFIRE) method for the monitoring of the enzyme conformation entrapped in carbon black particles [55]. Mazurenko et al also reported the resolution of enzyme partitions in carbon felts [21].…”
Section: Conductive Electrode Surfacesmentioning
confidence: 99%
“…The optical properties of carbon at mid‐infrared wavelengths can cause spectral band distortions and limit radiation throughput . Recently, a strategy based on attenuated total reflection (ATR) infrared sampling was shown to provide valuable insights into bioelectrocatalytic pathways for enzymes adsorbed to high surface area carbon . Excellent sensitivity was achieved toward ligands at the catalytic active site in measurements on films of a model enzyme system cast onto the ATR crystal …”
Section: Introductionmentioning
confidence: 99%